Alleviation effects of niacin supplementation on beef cattle subjected to heat stress: A metagenomic insight - Zou, Bicheng; Long, Fan; Xue, Fuguang; Qu, Mingren; Chen, Chuanbin; Zhang, Xian; Xu, Lanjiao (Frontiers in Microbiology, 2022)
The objective of this study was to investigate the alleviation effects of niacin supplementation on beef cattle subjected to heat stress. In the experiment, 36 Jinjiang bull cattle with a body weight of about 400±20.0kg were randomly divided into three treatments, each treatment contains four replicates, with 3 cattles in each replicate. Treatments included thermoneutral treatment (TN; 26℃±2℃), heat stress treatment, exposed to environmental temperature (HS; 33℃±2℃), and heat stress supplemented with niacin treatment (HN; high temperature + 800 mg/kg NA). Indicators included body temperature, respiratory rate, production performances, rumen fermentations, and rumen microbial diversity were measured. Results showed the addition of niacin reduced the body temperature and respiratory rate (P<0.05), but no significant effect on the production performances compared with heat-stressed beef cattle. HS treatment significantly increased body temperature and respiratory rate (P<0.01), while decreased the content of acetic acid, butyric acid, and total volatile fatty acids(P<0.05) compared with the TN treatment. Supplement of niacin did not affect ruminal fermentation parameters (P>0.05), but had a decreased tendency on A/P (P<0.1). Microbial diversity results showed that, at the phylum level, the relative abundance of Desulfobacterota in the HS treatment was increased compare with TN and HN treatment (P < 0.05). At the genus level, the relative abundance of Succiniclasticum and Family_XIII_AD3011_group in the HN treatment significantly proliferated compared with the HS treatment (P < 0.05). No significant discrepancies were observed for other bacteria. In conclusion, niacin supplementation may alleviate heat stress through proliferating those bacteria belong to the phylum Succiniclasticum, which may further contribute to the digestion of cellulose and the improvement of the metabolic function of Jinjiang cattle under heat stress conditions. This experiment provides a theoretical basis for exploring the alleviation methods of heat stress environmental factors on the rumen of beef cattles.